Pengaruh Latar Belakang Pendidikan Orang Tua Terhadap Pemahaman Toleransi Beragama Siswa Sekolah Dasar - Dede Hasanah (GENFABET: Generasi Pendidikan Dasar, 2024)
The influence of parents' educational background on the understanding of religious tolerance in elementary school students. This research is dilated by the hypothesis of the influence of the background of old oak education on the understanding of religious tolerance of elementary school students. The purpose of this study is to find out the influence of the background of parents' education on the understanding of religious tolerance of students. The subject of this study was a fourth-grade student who had a total of 60 students. Data collection techniques through surveys and observations. To learn the understanding of religious tolerance our students give questionnaires and to know the background of parents education researchers assign questions to students' last education of their parents. From the results of the correlations test, correlation hypotheses on religious tolerance variables, students have personal correlations of 0.599 and Sig.2-tailed. Thus it can be concluded that there is a significant link between the understanding of religious tolerance of students in the background of parents' education.